Shakespeare and the Second World War : memory, culture, identity - Makaryk, Irena R. (Irena Rima), 1951-; McHugh, Marissa, 1980- (University of Toronto Press, 2012)
The essays demonstrate how the wide variety of ways in which Shakespeare has been recycled, reviewed, and reinterpreted from 1939--1945 are both illuminated by and continue to illuminate the War today.